SUMUDU TRANSFORM FOR NATURAL GROWTH, DECAY AND COOLING - Rao, R. Umamaheshwar (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The aim of this paper is to demonstrate the applications of Sumudu Transform for solving the problems on principles such as Law of natural growth and decay and also on Newton’s law of cooling.